PENGARUH PERUBAHAN PERILAKU INDIVIDU DAN KARAKTERISTIK KEPRIBADIAN TERHADAP KINERJA PEGAWAI DI PT GOLDEN BLOSSOM SUMATRA (GBS) - Shindi Shindi; Reva Maria Valianti; Nisa’ Ulul Mafra (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to test the effect of individual behavior changes and personality characteristics on employee performance at PT Golden Blossom Sumatra (GBS). The population of this study included 181 employees at PT Golden Blossom Sumatra (GBS), the sample drawn was 108 respondents with a proportional stratified random sampling technique. The data analysis technique used in this study was the classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of hypothesis testing prove that there is an effect of individual behavior changes and personality characteristics simultaneously on employee performance at PT Golden Blossom Sumatra (GBS). The results of hypothesis testing prove the significant effect of individual behavior changes on employee performance and the significant influence of personality characteristics on employee performance at PT Golden Blossom Sumatra (GBS). The results of the determination coefficient show that individual behavior changes and personality characteristics can contribute to the performance of employees at PT Golden Blossom Sumatra (GBS), with a significant contribution of 89.5%. Keywords: Individual Behavior Changes; Personality Characteristics; Employee Performance